SPK Penerima Beasiswa PIP DI SDN Aranio 1 Menggunakan Metode SAW - Aulia, Zahratul; Fitriyadi, Fitriyadi (STMIK Banjarbaru, 2026)
This study aimed to develop a Decision Support System to determine the priority of prospective recipients of the Program Indonesia Pintar scholarship at SD Negeri Aranio 1. The problem faced was that the selection process was still carried out manually, requiring considerable time and resulting in less objective decisions. In addition, the number of scholarship quotas provided by the education authority varied in each period, making it difficult for the school to determine eligible recipients. The Simple Additive Weighting method was applied to rank students based on six criteria, namely parents' income, number of dependents, child status, parents' occupation, registration status in the Integrated Social Welfare Data, and ownership of the Prosperous Family Card. The calculation process was conducted through normalization and weighting to obtain the preference value of each student. The results showed that the system was able to generate scholarship recipient rankings automatically and consistently. Validation using Spearman Rank Correlation produced a correlation value of 0.8066, indicating a very strong relationship. Therefore, the developed system could be used to support scholarship recipient decision-making. Keywords: Decision Support System; Program Indonesia Pintar; Scholarship; Simple Additive Weighting; Spearman Rank Correlation. Abstrak Penelitian ini bertujuan untuk mengembangkan Sistem Pendukung Keputusan dalam menentukan prioritas calon penerima Beasiswa Program Indonesia Pintar di SD Negeri Aranio 1. Permasalahan yang dihadapi adalah proses seleksi yang masih dilakukan secara manual sehingga membutuhkan waktu yang lama dan kurang objektif, serta jumlah kuota penerima bantuan yang tidak pasti setiap periode. Metode Simple Additive Weighting digunakan untuk menentukan peringkat siswa berdasarkan enam kriteria, yaitu penghasilan orang tua, jumlah tanggungan, status anak, pekerjaan orang tua, status terdaftar dalam Data Terpadu Kesejahteraan Sosial, dan kepemilikan Kartu Keluarga Sejahtera. Proses perhitungan dilakukan melalui normalisasi dan pembobotan untuk memperoleh nilai preferensi setiap siswa. Hasil penelitian menunjukkan bahwa sistem mampu menghasilkan peringkat penerima beasiswa secara otomatis dan konsisten. Validasi menggunakan Spearman Rank Correlation menghasilkan nilai korelasi sebesar 0,8066 yang termasuk kategori hubungan sangat kuat, sehingga sistem dapat digunakan sebagai pendukung pengambilan keputusan penerima beasiswa. Kata Kunci: Sistem Pendukung Keputusan; Program Indonesia Pintar; Beasiswa; Simple Additive Weighting; Spearman Rank Correlation.